2019
DOI: 10.1002/ajh.25673
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and convergent consequences of splice factor mutations in myelodysplastic syndromes

Abstract: Myelodysplastic syndromes (MDS) are characterized by recurrent somatic alterations often affecting components of RNA splicing machinery. Mutations of splice factors SF3B1, SRSF2, ZRSR2 and U2AF1 occur in >50% of MDS. To assess the impact of spliceosome mutations on splicing and to identify common pathways/genes affected by distinct mutations, we performed RNA-sequencing of MDS bone marrow samples harboring spliceosome mutations (including hotspot alterations of SF3B1, SRSF2 and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…introns [29]. Similarly, we found that BPDCNs with ZRSR2 mutation or loss had increased IR compared to those without spliceosome mutations (Figure 4a).…”
Section: Unique Transcriptomic Features Of Spliceosome Mutated Bpdcnsupporting
confidence: 72%
See 2 more Smart Citations
“…introns [29]. Similarly, we found that BPDCNs with ZRSR2 mutation or loss had increased IR compared to those without spliceosome mutations (Figure 4a).…”
Section: Unique Transcriptomic Features Of Spliceosome Mutated Bpdcnsupporting
confidence: 72%
“…In contrast, ZRSR2 is uniquely necessary for proper splicing of U12 introns (0.3% of human introns), an evolutionarily conserved genomic feature with distinct branch and splice-site sequences [27,28]. In MDS, ZRSR2 mutations promote aberrant IR with a bias toward retention of U12-type introns [29]. Similarly, we found that BPDCNs with ZRSR2 mutation or loss had increased IR compared to those without spliceosome mutations (Figure 4a).…”
Section: Unique Transcriptomic Features Of Spliceosome Mutated Bpdcnmentioning
confidence: 60%
See 1 more Smart Citation
“…LUC7L2 mutations have been associated with shorter survival in patients with -7/del7q compared to patients with normal LUC7L2 expression [44,45]. LUCL7L2 has been found aberrantly spliced in MDS cases harboring SRSF2 small deletions [46]. Very rare mutations (<1%) have been found in other SF genes including SF3A1, SF1, PRPF40B, and U2AF2 [5,47].…”
Section: Other Splicing Factor Mutationsmentioning
confidence: 99%
“…Accordingly, in recent years, it has become clear that altering the function of DUB affects HSC homeostasis and may contribute to the onset of MDS and AML (Figure 4) by several mechanisms [254], as described for the DUBs BAP1, a tumor suppressor that cooperates with the polycomb group protein ASXL1 [255][256][257] or A20 [258,259], BRCC3 [260][261][262], USP7 [263,264], and USP10 [265]. DUB gene rearrangements have been reported in pediatric AML [266][267][268] and mis-splicing of USP9X-and its closely related protease USP24-was detected in SRSF2 mutant MDS samples [269]. Finally, consistently with a crucial role of DDR in HSC self-renewal [193,199,270], an increasing number of DUBs impacting on DDR have been implicated in HSC maintenance [271].…”
Section: Deubiquitinating Enzymes In Hscs Genome Stabilitymentioning
confidence: 96%